Club Cell Heme Oxygenase-1 Deletion: Effects in Hyperoxia-Exposed Adult Mice. (10th June 2020) - Dunigan-Russell, Katelyn; Silverberg, Mary; Lin, Vivian Y.; Li, Rui; Wall, Stephanie B.; Li, Qian; Nicola, Teodora; Gotham, John; Crowe, David R.; Vitiello, Peter F.; Agarwal, Anupam; Tipple, Trent E.
Abstract : Thioredoxin reductase-1 (TXNRD1) inhibition activates nuclear factor (erythroid-derived 2)-like 2 (Nrf2) responses and prevents acute lung injury (ALI). Heme oxygenase-1 (HO-1) induction following TXNRD1 inhibition is Nrf2-dependent in airway epithelial (club) cells in vitro . The influence of club cell HO-1 on lung development and lung injury responses is poorly understood. The present studies characterized the effects of hyperoxia on club cell-specific HO-1 knockout (KO) mice. These mice were generated by crossing Hmox1 flox mice with transgenic mice expressing cre recombinase under control of the club cell-specific Scgb1a1 promoter. Baseline analyses of lung architecture and function performed in age-matched adult wild-type and KO mice indicated an increased alveolar size and airway resistance in HO-1 KO mice. In subsequent experiments, adult wild-type and HO-1 KO mice were either continuously exposed to >95% hyperoxia or room air for 72 h or exposed to >95 hyperoxia for 48 h followed by recovery in room air for 48 h. Injury was quantitatively assessed by calculating right lung/body weight ratios (g/kg). Analyses indicated an independent effect of hyperoxia but not genotype on right lung/body weight ratios in both wild-type and HO-1 KO mice. The magnitude of increases in right lung/body weight ratios was similar in mice of both genotypes. In the recovery model, an independent effect of hyperoxia but not genotype was also detected. In contrast to the continuous exposure model, right lung/body weight ratio mice were significantly elevated in HO-1 KO but not wild-type mice. Though club cell HO-1 does not alter hyperoxic sensitivity in adult mice, it significantly influences lung development and resolution of lung injury following acute hyperoxic exposure.